"Irish Nights": Paratheatrical Performances of Melodrama on and off the Belfast Stage. Issue 2 (25th April 2018) - Phelan, Mark
Abstract : Until relatively recently, melodrama has been an unfairly maligned genre of theatre history; its pejorative associations based on the prejudiced assumptions that its aesthetics of excess (in terms of its extravagant emotion, sensationalism and popularity amongst predominantly working class audiences) meant, therefore, that it was for simpletons. What Walter Benjamin excoriated as the "ancient lament that the masses seek distraction whereas art demands concentration from the spectator" fuelled bourgeois disdain for this theatrical form and the derision of the Theatrical Inquisitor 's dismissal of melodrama as "aris[ing] from an inertness in the minds of the spectators, and a wish to be amused without the slightest exertion on their own parts, or any exercise whatever of their intellectual powers" remained the dominant critical response throughout the nineteenth century. Indeed, such views continued well into the twentieth century and certainly characterized the modernist reactions of the founding figures of the Irish national theatre in this period. Frank Fay, cofounder of the National Dramatic Society, denounced both the aesthetics of Dublin's Queen's Theatre as the "home of the shoddiest kind of melodrama, " and the intelligence of its audiences who, "wouldn't, at present, understand anything else."